Сontemporary pragmatics and vectors of combating cybercrime in the context of information and economic security strengthening - Vivchar, Oksana (Актуальні проблеми правознавства, 2017)
Key problem aspects of combating cybercrime activity in modern globalization conditions have been considered. In the process of study the main indicators of cybercrime analysis and identification of tasks diagnostic in the field of information technologies have been grounded. Based on this information the ways of combating cybercrime in the context of strengthening information and economic security have been proposed.